Hydrodynamic activities and lifestyle preferences synergistically drive prokaryotic community assembly processes in the dual fronts system of the Yangtze River Estuary - Lu, Han; Ma, Zhonglin; Su, Lei; Du, Yunfei; Zhou, Kun; Wang, Peng (Frontiers in Microbiology, 2025)
The dual fronts system of the Yangtze River Estuary plays a critical role in the hydrodynamic-biological coupling mechanisms, whose frontal effects stimulate marine microorganisms to adapt to environmental fluctuation. However, the synergistic mechanisms driving prokaryotic community assembly in the dual fronts system remain poorly conceptualized, particularly regarding lifestyle preferences (free-living vs. particle-associated). By integrating physicochemical parameter analysis and high-throughput 16S rRNA amplicon sequencing, we described the unique prokaryotic community and quantified the assembly processes of particle-associated and free-living prokaryotic sub-communities. The effects of the dual fronts reshaped the prokaryotic community by differentiating the abundant and rare species of the particle-associated and free-living communities. Rhodobacteraceae, Flavobacteriaceae, and Cyanobiaceae played vital roles in the prokaryotic community across three water masses, while the rare species exhibited distinct differences. The prokaryotes in the water mass between the sediment front and plume front preferred a particle-associated lifestyle, while free-living was the preferred lifestyle in other water masses. Stochastic dispersal limitation and deterministic homogeneous selection dominated prokaryotic community assembly in the dual fronts system. Free-living prokaryotes with high environmental sensitivity were influenced by homogeneous selection in community assembly, and particle-associated prokaryotes were easily constrained by particle-mediated dispersal. The vigorous hydrodynamic activities could stimulate the attachment-detachment on particulates of prokaryotes, resulting in alterations to assembly mechanisms and participative species. Ultimately, hydrological activities and lifestyle preferences collaborated to determine the assembly mechanisms of meta-community and sub-community. This study pioneers the linkage between dual frontal hydrodynamics and microbial lifestyle-specific assembly, providing a predictive framework for prokaryotic community responses under tumultuous environmental fluctuations.